Examining the use of audiovisual technology to supportthe teaching of the listening skill in 1st, 2nd and 3rd years of bachillerato at “Hernán Gallardo Moscoso” high school, Academic period 2013-2014 - Robles Jumbo, Ana Elizabeth (2015)
This descriptive research work had the purpose of determining how the use of audiovisual technology influenced on the development of the listening skill of the English Language in the students of 1st , 2nd and 3rd years of Bachillerato at “Hernan Gallardo Moscoso” High school during the academic period 2013-2014. The scientific method was used along the study. A researcher-made questionnaire was applied to 57 students and 2 teachers. Observations were carried out in order to collect information. The data reported were organized, analyzed and interpreted in order to obtain the conclusions. The findings revealed that even though all respondents were aware of the role of technology in the development of the listening skill; the time devoted to listening practice and the quality of the listening activities were inadequate. The insufficient number of existing technology devices and the teachers’ restricted use made the situation more critical